Prevalencia de infección de herida quirúrgica en pacientes con profilaxis antimicrobiana en cesárea programada - Martínez Padrón, Hadassa Yuef; Polendo-Posadas, Luis Eduardo; Ramos-Hernández, Julia Demetria; Vargas González, Domingo; Paredes Sánchez, Francisco Alejandro; Rivera Vázquez, Patricia (Horizonte Sanitario, 2022)
Objective: To determine the prevalence of surgical wound infections in scheduled HRAEVcesarean sections.Materials and method: Retrospective, descriptive, observational cross-sectional study todetermine the prevalence of IHC in patients undergoing scheduled cesarean section withantibiotic prophylaxis in HRAEV.Results: 185 records of patients undergoing scheduled cesarean section were evaluated,aged between 28 to 37 years (48.1%) with an average weight of 81 kg (SD = 10.1) withan average body mass index (BMI) of 30 (SD = 4.24) that is, a BMI between 25.76 and34.24. Of these, 4 patients (2.16%) presented surgical wound infection during scheduledcesarean section, who received ceftriaxone as PA greater than 120 minutes prior to skinincision, these patients are classified as ASA II and had a BMI greater than 30 kg/m2 andwithout recorded comorbidities. The most frequent antibiotic prophylaxis time in patientsundergoing scheduled cesarean section was >120 minutes (34.08%) and ceftriaxone wasadministered in 84.86% of the population, which is mostly ASA II (97.83%). 100% of thewounds were superficial.Conclusions: In the present study, it was found that the prevalence of IHC in cesareansections scheduled in HRAEV was 2.16%, a figure that is below the worldwide prevalence,given that the selected patients did not have some of the risk factors. added risk that increasedthe risk of SSI compared to other studies.Keywords: Surgical wound, Infection, Antibiotic prophylaxis, Cesarean section